Acid-functionalized ion exchange materials
By designing an ion exchange material containing a polymer support, acid groups and polymer layer, the problems of instability of existing materials under alkaline conditions and low separation efficiency of haloacetic acid are solved, and the basic stability of the material and efficient separation of haloacetic acid are achieved.
Patent Information
- Application Number
- CN202380057061.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-05
- Filing Date
- 2023-07-28
- Publication Date
- 2025-03-04
AI Technical Summary
The existing ion exchange materials are unstable under alkaline conditions, making it difficult to effectively separate halogenated acetic acid, and the retention time of standard anions and halogenated acetic acid is difficult to adjust.
An ion exchange material including a polymer support, directly linked acid groups and covalently linked polymer layer is employed, which is spatially separated by the acid groups and anion exchange groups in the range of 0.05-1.05 mmol/gram of acid groups, optimizes the thickness and structure of the polymer layer to achieve basic stability of the material and efficient separation of haloacetic acid.
It realizes stable ion exchange under alkaline conditions, improves the separation efficiency and selectivity of halogenated acetic acid, shortens the retention time of halogenated acetic acid, and is suitable for the analysis and preparation of separation.
Smart Images

Figure CN119562855A_ABST
Abstract
Description
[0001] The present invention relates to ion exchange materials for use as stationary phases in analytical or preparative separation processes, in particular ion exchange materials for the separation of anions, preferably halogenated acetic acids. The present invention also relates to methods for the manufacture of such ion exchange materials, chromatographic columns filled with the ion exchange materials, methods for the chromatographic separation of analytes and uses of the ion exchange materials.
[0002] Ion exchangers are usually made of particulate materials that carry a charge on their surface, enabling them to retain ions. Anion exchangers are often based on cationic ammonium compounds, although phosphonium and arsonium ions are also known. For purely electrostatic interactions, the retention time is determined by Coulomb's law. Therefore, only the charge of the anion affects the retention time of the latter. However, when ion chromatography is performed in aqueous solutions, other factors influence the retention behavior, such as the hydration of the anion and the hydration of the exchange groups. The polarizability of the ions involved and the weaker secondary interactions between the analyte and the exchange matrix also play a role.
[0003] In WO2020208026A1, secondary interactions between the analyte and the exchange matrix are reduced by hydrophilizing the polymer core of the particles. The resulting alcohol groups can be used to connect the hydrophilic polymer and the anion exchange material. However, the lack of negative charges on the particles leads to a long retention time of dichloroacetic acid, which is particularly important for the analysis of drinking water according to EPA 300.1.
[0004] US20050181224 describes another method for reducing the secondary interaction of analyte and exchange matrix, wherein first sulfonated polymer matrix particles are coated with hyperbranched polymer layers on the negatively charged polymer matrix. Repulsive interactions prevent anions from diffusing into the hydrophobic core and pores. The particles are highly sulfonated, which requires many hyperbranched cycles to introduce enough ammonium groups to separate anions. In such hyperbranched anion exchangers, capacity and selectivity cannot vary independently. The influence of hyperbranching is also described in C. Pohl, C. Saini, J. Chromatogr. A, 1213, (2008), 37-44.
[0005] AS Uzhel et al., J. Chromatogr. A 1482 (2017) 57–64 describe anion exchangers with a covalently bonded hyperbranched functionalized ion exchange layer comprising negatively charged functional groups in close proximity to positively charged ammonium groups. A variation in the selectivity can be obtained by varying the position and number of carboxylic acid groups in the hyperbranched layer. Good selectivity for weakly retained organic acids and oxyhalides was obtained. However, a disadvantage of anion exchangers is that due to the proximity of positive and negative charges, the net charge is zero in the small area where the ion exchange occurs, which has a negative impact on the separation properties of certain anions and the capacity of the column. Capacity and selectivity cannot be adjusted independently. The pH stability required for the separation material cannot be guaranteed.
[0006] EP4019126 describes a method for preparing a solid carrier to prevent the co-elution of haloacetic acid with some oxohalides and standard anions. However, the retention time relative to the standard anion can not be regulated by the chromatographic column material. Although disclosed material realizes the good separation of various anions, the retention time of some haloacetic acids is quite long.
[0007] Therefore, at least one object of the present invention is to overcome the shortcomings of the prior art. In particular, an object of the present invention is to provide an ion exchange material that realizes good separation of haloacetic acid except standard anions, which is sufficiently stable under alkaline conditions and provides elution with a shortened retention time within a reasonable time frame. Another object is to provide a method for making such an ion exchange material. A further object of the present invention is to provide a chromatographic column with such an ion exchange material to provide a method for separating analytes, and to provide the purposes of such an ion exchange material. Another object of the present invention is to provide a method for regulating the retention time of haloacetic acid relative to standard anions in the preparation of a post.
[0008] The object is achieved by the subject matter of the independent claims. Specific embodiments are described in the dependent claims.
[0009] A first aspect of the present invention relates to an ion exchange material for use as a stationary phase in an analytical or preparative separation process, in particular an ion exchange material for the separation of anions, preferably halogenated acetic acids. The ion exchange material comprises
[0010] - polymer carrier,
[0011] - an acid group directly attached to the surface of the polymer support, wherein the acid group is selected from: a sulfonic acid group, a carboxylic acid group or a combination thereof,
[0012] - a polymer layer covalently attached to the surface of the polymer support, wherein the polymer layer comprises anion exchange groups,
[0013] The amount of acid groups is in the range of 0.05-1.05 mmol / g polymer support, preferably 0.1-0.9 mmol / g, particularly preferably 0.16-0.85 mmol / g. The acid groups and anion exchange groups are spatially separated, preferably by the polymer layer by at least 10 nm, preferably at least 50 nm, most preferably at least 100 nm.
[0014] Preferably, the thickness of the polymer layer does not exceed 3000 nm, preferably does not exceed 500 nm, more preferably does not exceed 400 nm, most preferably does not exceed 300 nm.
[0015] Ion exchange materials show good alkaline stability and capacity under the chromatographic conditions of ion exchange. It is also found that the acid groups in the above-mentioned range realize the very good separation of haloacetic acid, particularly except standard anions, have shorter retention time and therefore have reasonable elution time. The theoretical plate number can be associated with the amount of carboxylic acid groups, realizes the regulation of material properties, and along with the increase of the amount of acid groups, causes the peak of haloacetic acid in the chromatogram to be sharper. Not bound by theory, it is believed that the acid groups on the polymer carrier surface repel anions, which prevents the interaction of anions with the core of the polymer carrier. The distance between anion exchange groups and acid groups is large enough to avoid zero net charge in the small region where ion exchange occurs, which further improves the separation of analytes.
[0016] The standard anions mentioned in the text are fluoride, chloride, nitrite, bromide, and nitrate.
[0017] Due to the increasing number of upcoming standards (China GBT 5750.10-2020) and existing standards (US EPA 557), the separation of halogenated acetic acids is becoming more and more important, second only to the separation of standard anions. These standards are used to identify disinfection byproducts at low concentrations. Low concentrations require small peaks and short retention times for good enough identification.
[0018] The amount of negative charge on the ion exchange material is determined by titration methods, as described in further detail below.
[0019] Preferably, the polymer layer is linked to the polymer support via oxygen or nitrogen bonds.
[0020] The polymer carrier may be present in the form of particles, in the form of a gel or in the form of a film. Particles are preferred.
[0021] The polymer layer is preferably attached directly to the polymer support, ie not via acid groups.
[0022] "Spatially separated" refers to separation both by bond and by space.
[0023] The distance between the acid group and the anion exchange group was calculated based on the bond length between these groups.
[0024] Polymer carriers can
[0025] - derived at least in part from an aromatic hydrocarbon compound having at least two vinyl or allyl substituents, preferably derived at least in part from a divinylbenzene monomer; and
[0026] - derived in part from a monomer selected from the group consisting of ethylvinylbenzene, vinyl acetate, styrene, and any combination thereof.
[0027] The relative amount of the aromatic compound having at least two vinyl or allyl substituents, preferably a divinylbenzene derived monomer, is preferably at least 50% by weight.
[0028] The polymer support may be derived solely from styrene and divinylbenzene (DVB) monomers.
[0029] For example, the polymer may be a polystyrene-divinylbenzyl (PS / DVB) polymer, most preferably PS / DVB derived from 55% divinylbenzene in ethylvinylbenzene.
[0030] Polystyrene-divinylbenzene polymers can be readily used as support materials by different synthesis methods known in the art.
[0031] The polymer support preferably comprises open pores, preferably with an average pore size of at most 60 nm.Even more preferably, the pores are micropores and / or mesopores according to the IUPAC definition, as can be measured by nitrogen adsorption in the BJH model as further described below.
[0032] Advantageously, the polymer layer is derived from
[0033] - reaction of a polymeric support, preferably a hydrophilized polymeric support, with an oligo- or polyamine, or
[0034] - Reaction of a polymer support, preferably a hydrophilized polymer support, with at least one polyfunctional compound comprising at least one first functional group reactive with amine and / or hydroxyl groups, preferably an epoxy group, and at least one second functional group reactive with amine and / or hydroxyl groups.
[0035] For example, the oligoamine, polyamine or at least one multifunctional compound can be covalently coupled to the polymer support via an aldehyde group, a ketone group or a hydroxyl group on the polymer support, as will be described in further detail below.
[0036] Alternatively, the polymer layer may be derived from
[0037] - reaction of a polymer support, preferably a hydrophilized polymer support, with at least one polyfunctional compound comprising at least one first functional group reactive with amine and / or hydroxyl groups, preferably an epoxy group, and at least one second functional group reactive with amine and / or hydroxyl groups, followed by
[0038] - Reaction with oligo- or polyamines.
[0039] The addition of a polymer layer or the composition of the polymer layer enables further adjustment of the selectivity of the ion exchange material.
[0040] The polymer layer can be crosslinked with at least one polyfunctional compound. Crosslinking of the polymer layer achieves a further improvement in the material properties, in particular the separation of haloacetic acids, more particularly the separation of monochloroacetic acid and monobromoacetic acid.
[0041] Preferably, at least one polyfunctional compound is selected from
[0042] - epoxides, in particular 1,4-butanediol diglycidyl ether, trimethylolpropane triglycidyl ether, poly(ethylene glycol) diglycidyl ether, resorcinol diglycidyl ether, glycerol diglycidyl ether, glycidol;
[0043] - organic halogen compounds, in particular epichlorohydrin, epibromohydrin, 1,1′-oxybis[2-(2-chloroethoxy)ethane], 1,2-bis(2-chloroethoxy)ethane, bis(2-chloroethyl)ether, 1-chloro-3-iodopropane, 1,4-dibromobutane, 1,3-dibromopropane;
[0044] - Aldehydes, especially glutaraldehyde.
[0045] The advantage of at least one multifunctional compound is that it provides multiple modifications of the material. The selectivity can be adjusted by adjusting the hydrophilicity or hydrophobicity. In particular, the hydrophilicity of 1,4-butanediol diglycidyl ether (BDGE) is beneficial to the selectivity of the haloacetic acid.
[0046] The anion exchange groups are preferably quaternary ammonium groups, most preferably quaternary ammonium groups produced by reaction with glycidyl trimethyl ammonium chloride, glycidyl methyl diethanol ammonium chloride and glycidyl triethyl ammonium chloride; or produced by reaction with tertiary amines, such as: N-methyl-2-pyrrolidone, N-methylmorpholine, N-methylpyrrolidone, N,N-dimethylethanolamine, N-methyldiethanolamine, N-methylpiperidine, N-ethylpiperidine, trimethylamine, triethylamine.
[0047] It is also possible to use charged phosphine groups as anion exchange groups.
[0048] Preferably, the oligo- or polyamine is selected from polyallylamine, linear or branched polyethyleneimine (PEI), poly(2-methylaziridine); preferably branched PEI.
[0049] Preferably, the ion exchange material comprises
[0050] - polymer carrier,
[0051] - an acid group directly attached to the surface of the polymer support, wherein the acid group is selected from: a sulfonic acid group, a carboxylic acid group or a combination thereof,
[0052] - A polymer layer covalently attached to the surface of a polymer support.
[0053] The polymer layer may be
[0054] (i) is derived from an oligo- or polyamine and is attached to the polymer layer of the support via reductive amination of the polymer support, or
[0055] (ii) or a polymer layer derived from the reaction of at least one multifunctional compound comprising at least one first functional group reactive with amine and / or hydroxyl groups, preferably an epoxy group, and at least one second functional group reactive with amine and / or hydroxyl groups.
[0056] The polymer layer (i) or the polymer layer (ii) may contain an anion exchange group.
[0057] Preferably, the amount of acid groups of the material having the polymer layer (i) is in the range of 0.41-1.05 mmol / g polymer support, preferably 0.65-1.05 mmol / g, particularly preferably 0.85-1.05 mmol / g. Preferably, the amount of acid groups of the material having the polymer layer (ii) is in the range of 0.05-0.19 mmol / g polymer support, preferably 0.05-0.16 mmol / g, particularly preferably 0.05-0.10 mmol / g. For (i) and (ii), the acid groups and the anion exchange groups are spatially separated, preferably by at least 10 nm, preferably at least 50 nm, most preferably at least 100 nm, by the polymer layer.
[0058] Lower amounts of acid groups still provide very good separation and reasonable elution times for the haloacetic acids compared to standard anions, but also provide adequate stability against alkaline conditions. Surprisingly, it was found that above 0.25 mmol / g carboxylic acid groups, the material is not permanently stable under strongly alkaline conditions and if it contains oxygen bonds, such as in the case of polymer (ii), starts to lose its ability over time. However, higher amounts of acid groups achieve even earlier elution times while having high alkaline stability.
[0059] For higher amounts of carboxylic acid groups above 0.41 mmol / g, polymer layers with nitrogen bonds show particularly good alkaline stability, such as in the case of polymer (i).
[0060] Therefore, the long-acting ion exchange material has good separation properties of haloacetic acid relative to standard anions under strongly alkaline conditions.
[0061] Preferably, the polymer layer (i) is bonded to the polymer support via a nitrogen bond and the polymer layer (ii) is bonded to the polymer support via an oxygen bond.
[0062] Advantageously, the polymer layer is derived from
[0063] - (i) reaction of a polymeric support, preferably a hydrophilized polymeric support, with an oligo- or polyamine, or
[0064] - (ii) reaction of a polymer support, preferably a hydrophilized polymer support, with at least one polyfunctional compound comprising at least one first functional group reactive with amine and / or hydroxyl groups, preferably an epoxy group, and at least one second functional group reactive with amine and / or hydroxyl groups.
[0065] For example, the oligoamines and polyamines can be covalently coupled to the polymer via aldehyde groups or ketone groups; the at least one multifunctional compound can be covalently coupled to the polymer support via hydroxyl groups on the polymer support.
[0066] As mentioned above, the polymer layer (i) or the polymer layer (ii) may be crosslinked with at least one polyfunctional compound.
[0067] The anion exchange groups are preferably quaternary ammonium groups, and for polymer layer i), the most preferred are quaternary ammonium groups produced by reaction with glycidyl trimethyl ammonium chloride, glycidyl methyl diethanol ammonium chloride and glycidyl triethyl ammonium chloride. For polymer layer ii), the anion exchange groups are preferably produced by reaction with tertiary amines, such as: N-methyl-2-pyrrolidone, N-methylmorpholine, N-methylpyrrolidone, N,N-dimethylethanolamine, N-methyldiethanolamine, N-methylpiperidine, N-ethylpiperidine, trimethylamine, triethylamine.
[0068] Another aspect of the invention relates to a method for producing an ion exchange material having an amount of acid groups in the range of 0.05-1.05 mmol / g polymer support, preferably 0.1-0.9 mmol / g, particularly preferably 0.16-0.85 mmol / g, and each acid group is spatially separated from an anion exchange group by at least 10 nm, preferably at least 50 nm, most preferably at least 100 nm, for use as a stationary phase in an analytical or preparative separation process. The ion exchange material is preferably an ion exchange material as described above. The method comprises the following steps:
[0069] a) providing a polymer carrier;
[0070] b) subjecting the polymer support to an oxidation treatment in the presence of an oxidizing agent, preferably a peracid;
[0071] c) partially reducing the polymer support obtained in step b) with a reducing agent to obtain a hydrophilized polymer support;
[0072] d) reacting the product of step c) with at least one polymer or polymer precursor to obtain a polymer layer on the polymer support;
[0073] e) Introducing anion exchange groups into the polymer layer.
[0074] Steps c) and d) are carried out completely or partially simultaneously or sequentially.
[0075] Preferably, the thickness of the polymer layer does not exceed 3000 nm, preferably does not exceed 500 nm, more preferably does not exceed 400 nm, most preferably does not exceed 300 nm.
[0076] Surprisingly, it has been found that the partial reduction in step c) correlates with the amount of acid groups formed on the polymer support, thus enabling an adjustment of the properties of the polymer support as ion exchange material.
[0077] The resulting ion exchange material shows good stability and high capacity. The amount of acid groups achieves good separation of haloacetic acid, second only to standard anions, and the retention time of haloacetic acid is shorter. The peak of haloacetic acid is sharper in the chromatogram and the number of theoretical plates increases. The distance between the anion exchange group and the acid group is large enough to avoid a net charge of zero in the small area where the ion exchange occurs.
[0078] The polymer support obtained after step b) and / or c) is a substantially hydrophilic polymer support. "Substantially hydrophilic" means that the polymer support forms a suspension in water. 1 g of the hydrophilic polymer support is suspended in 20 mL of water using a Phoenix RA-VA vortex mixer and the solution is shaken for 30 seconds. If sufficiently hydrophilic, the particles of the polymer support remain suspended for at least 15 minutes.
[0079] Step b) may result in the formation of carboxylic acid groups (COOH), and step c) may partially result in the formation of hydroxyl groups (OH) on the polymer support together with the remaining carboxylic acid groups. Most preferably, the hydroxyl groups of the polymer support react with the polymer or polymer precursor in step d) to produce oxygen bonds between the polymer support and the polymer layer.
[0080] The oxidizing agent in step b), preferably a peracid, may be generated in situ.
[0081] The polymer precursor may be any molecule capable of forming a polymer layer by multiple reactions with itself or other molecules, such as multifunctional compounds, polyamines or oligoamines as monomers, as further described below.
[0082] Step b) or step c) may be followed by an additional treatment in the presence of sulfuric acid. In any case, this step is performed before step d). This step can achieve the introduction of sulfonic acid groups into the polymer support, providing a polymer support to which carboxyl and sulfonic acid groups are directly attached. Most preferably, this step is performed in the presence of acetic acid as a solvent.
[0083] The combination of sulfonic acid groups with carboxylic acid groups pushes the haloacetic acid further to an earlier retention time compared to a similar amount of carboxylic acid alone. This is most likely due to the pk of the sulfonic acid group (SO3H) compared to the carboxylic acid group (COOH). a Lower.
[0084] A particular advantage of this method compared to a polymer support having only sulfonic acid groups is that the polymer layer can still be covalently attached to the polymer support and because only a small amount of sulfonic acid groups are added and a small amount of sulfonic acid groups are combined with carboxylic acid groups, for example in a ratio of 0.15 mmol / g sulfonic acid groups to 0.23 mmol / g carboxylic acid groups, the resolution of the injection peak for fluoride ions (IP / F) is still very good.
[0085] The amount of peracid in step b) is preferably generated in the presence of acid and hydrogen peroxide, wherein the ratio between acid and H2O2 (mol / mol) is in the range of 1.0:0.12 to 1.0:0.72, preferably 1.0:0.14 to 1.0:0.52, most preferably 1.0:0.16 to 1.0:0.44.
[0086] Most preferably, 35% hydrogen peroxide is used, added in an amount to achieve the above ratio.
[0087] The reducing agent may be selected from lithium aluminum hydride, sodium borohydride, sodium triacetoxyborohydride, sodium cyanoborohydride.
[0088] The amount of the reducing agent in step c) may be in the range of 0.03 g to 1.0 g, preferably 0.05 g to 0.8 g, most preferably 0.1 g to 0.5 g, per 1.0 g of the polymer carrier obtained in step b), based on the dry weight of the polymer carrier.
[0089] "Dry weight" means that the polymer carrier or polymer present is ≥ 98%, i.e. the moisture content does not exceed 2%. The moisture content was analyzed using a compact moisture analyzer MA 35 from Sartorius.
[0090] The amount of reducing agent achieves a partial reduction of the carboxylic acid groups present and thus an adjustment of their amount, which in turn achieves an adjustment of the selectivity and the number of theoretical plates.
[0091] The polymer support in step a) is preferably
[0092] - derived at least in part from an aromatic hydrocarbon compound having at least two vinyl or allyl substituents, preferably derived at least in part from a divinylbenzene monomer; and
[0093] - derived in part from a monomer selected from the group consisting of ethylvinylbenzene, vinyl acetate, styrene, and any combination thereof.
[0094] The relative amount of the aromatic compound having at least two vinyl or allyl substituents, preferably a divinylbenzene derived monomer, is preferably at least 50% by weight.
[0095] For example, the polymer may be a polystyrene-divinylbenzyl (PS / DVB) polymer, most preferably PS / DVB produced from 55% divinylbenzene in ethylvinylbenzene. Copolymers consisting only of polystyrene and divinylbenzene structural units are also conceivable.
[0096] The polymer support provided in step a) is preferably open-porous, preferably having an average pore size of at most 60 nm. Even more preferably, the pores are micropores and / or mesopores according to the IUPAC definition, measurable by nitrogen adsorption in the BJH model as further described below.
[0097] Step d) may include the following steps
[0098] - reacting the support material obtained in step b) with an oligo- or polyamine, preferably in the presence of a reducing agent, or
[0099] - reacting the support material obtained in step c) with at least one polyfunctional compound as polymer precursor, said polyfunctional compound comprising at least one first functional group reactive with amine and / or hydroxyl groups, preferably an epoxy group, and at least one second functional group reactive with amine and / or hydroxyl groups, preferably an epoxy group.
[0100] In the first case, steps c) and d) are preferably carried out simultaneously, whereas in the second case, steps c) and d) are preferably carried out sequentially.
[0101] Alternatively, step d) may comprise the following steps:
[0102] - reacting the support material obtained in step c) with at least one polyfunctional compound as polymer precursor material, said polyfunctional compound comprising at least one first functional group reactive with amine and / or hydroxyl groups, preferably an epoxy group, and at least one second functional group reactive with amine and / or hydroxyl groups, preferably an epoxy group, and subsequently
[0103] - Reaction with oligo- or polyamines.
[0104] The amount of the at least one polymer or polymer precursor, in particular an oligoamine, a polyamine or at least one multifunctional compound in step d) may be in the range of 0.1 g to 10.0 g, preferably 0.5 g to 8.0 g, most preferably 1.5 g to 7.0 g, per 1 g of the polymer support obtained in step c), based on the dry weight of the polymer support.
[0105] Furthermore, step e) is preferably followed by a crosslinking step f): treating the reaction product resulting from step e) with at least one polyfunctional compound.
[0106] Advantageously, the polyfunctional compound(s) are selected from
[0107] - epoxides, in particular 1,4-butanediol diglycidyl ether, trimethylolpropane triglycidyl ether, poly(ethylene glycol) diglycidyl ether, resorcinol diglycidyl ether, glycerol diglycidyl ether, glycidol;
[0108] - organic halogen compounds, in particular epichlorohydrin, epibromohydrin, 1,1′-oxybis[2-(2-chloroethoxy)ethane], 1,2-bis(2-chloroethoxy)ethane, bis(2-chloroethyl)ether, 1-chloro-3-iodopropane, 1,4-dibromobutane, 1,3-dibromopropane;
[0109] - Aldehydes, especially glutaraldehyde.
[0110] In step e), the polymer carrier of step d) is preferably reacted with a quaternary ammonium or tertiary amine, wherein the quaternary ammonium is preferably selected from: glycidyl trimethyl ammonium chloride, glycidyl methyl diethanol ammonium chloride and glycidyl triethyl ammonium chloride; the tertiary amine is preferably selected from: N-methyl-2-pyrrolidone, N-methylmorpholine, N-methylpyrrolidone, N,N-dimethylethanolamine, N-methyldiethanolamine, N-methylpiperidine, N-ethylpiperidine, trimethylamine, triethylamine.
[0111] The oligo- or polyamine may be selected from polyallylamine, linear or branched polyethyleneimine (PEI), poly(2-methylaziridine); branched PEI is preferred.
[0112] In a subsequent step to step e) or f), a hydrolysis step, in particular a basic hydrolysis step, may be carried out in order to eliminate any esters formed and to hydrolyze the ester bonds back to the carboxylic acid groups.
[0113] Preferably, the method comprises producing an ion exchange material having an amount of acid groups (i) in the range of 0.41-1.05 mmol / g polymer support, preferably 0.65-1.05 mmol / g, particularly preferably 0.85-1.05 mmol / g; or an amount of acid groups (ii) in the range of 0.05-0.19 mmol / g polymer support, preferably 0.05-0.16 mmol / g, particularly preferably 0.05-0.10 mmol / g; and each acid group is spatially separated from the anion exchange group by at least 10 nm, preferably at least 50 nm, most preferably at least 100 nm, which is used as a stationary phase in an analytical or preparative separation process. The ion exchange material is preferably an ion exchange material as described above. The method may comprise the following steps:
[0114] a) providing a polymer carrier;
[0115] b) subjecting the polymer support to an oxidation treatment in the presence of an oxidizing agent, preferably a peracid;
[0116] c) partially reducing the polymer support obtained in step b) with a reducing agent to obtain a hydrophilized polymer support;
[0117] d) the product of step c) and
[0118] (i) reacting at least one oligoamine or polyamine to obtain a polymer layer on a polymer support; or
[0119] (ii) reacting at least one polyfunctional compound comprising at least one first functional group reactive with amine and / or hydroxyl groups, preferably an epoxy group, and at least one second functional group reactive with amine and / or hydroxyl groups, to obtain a polymer layer on the polymer support;
[0120] e) introducing anion exchange groups into the polymer layer obtained in step d)(i) or the polymer layer obtained in step d)(ii).
[0121] Steps c) and d)(i) are preferably carried out simultaneously, and steps c) and d)(ii) are preferably carried out in whole or in part sequentially.
[0122] As mentioned previously, the material is particularly stable under alkaline conditions and has very good separation properties for haloacetic acids relative to standard anions.
[0123] Most preferably, the hydroxyl groups of the polymer support react with the polymer in step d)(ii) to produce oxygen bonds between the polymer support and the polymer layer. The nitrogen-containing bonds are preferably the result of the reaction of the polymer support with an oligo- or polyamine in step d)(i).
[0124] Step d) may include the following steps
[0125] (i) reacting the support material obtained in step b) with an oligo- or polyamine, preferably in the presence of a reducing agent, or
[0126] (ii) reacting the support material obtained in step c) with at least one polyfunctional compound as polymer precursor, the polyfunctional compound comprising at least one first functional group reactive with amine and / or hydroxyl groups, preferably an epoxy group, and at least one second functional group reactive with amine and / or hydroxyl groups, preferably an epoxy group.
[0127] In the first case (i), steps c) and d) are preferably carried out simultaneously, whereas in the second case (ii), steps c) and d) are preferably carried out sequentially.
[0128] In step e), the polymer carrier of step d) (i) is preferably reacted with a quaternary ammonium, preferably selected from the group consisting of glycidyl trimethyl ammonium chloride, glycidyl methyl diethanol ammonium chloride and glycidyl triethyl ammonium chloride. The polymer carrier of step d) ii) is preferably reacted with a tertiary amine, preferably selected from the group consisting of N-methyl-2-pyrrolidone, N-methylmorpholine, N-methylpyrrolidine, N,N-dimethylethanolamine, N-methyldiethanolamine, N-methylpiperidine, N-ethylpiperidine, trimethylamine, triethylamine.
[0129] Another aspect of the present invention relates to an ion exchange material for use as a stationary phase in an analytical or preparative separation process, in particular a chromatographic process, obtainable by the above-described process.
[0130] Another aspect of the present invention relates to a chromatography column filled with the ion exchange material as described above, in particular an ion exchange chromatography column.
[0131] Surprisingly it was found that such a column enables the determination of haloacetic acids due to the improved separation of these compounds in a shorter time.
[0132] In addition, another aspect of the present invention relates to a method for chromatographic separation of an analyte, in particular an anion, more preferably a halogenated acetic acid, most preferably monochloroacetic acid (MCA), monobromoacetic acid (MBA), dichloroacetic acid (DCA) and dibromoacetic acid (DBA). The method comprises the step of contacting a solution containing the analyte with an ion exchange material as described above, in particular passing the solution through a chromatographic column as described above.
[0133] The following compounds can also be separated: trichloroacetic acid, tribromoacetic acid, bromo-dichloroacetic acid, chloro-dibromoacetic acid and dichloropropionic acid.
[0134] Most preferably, the chromatographic separation method may be performed according to EPA 557.
[0135] A further aspect of the present invention relates to the use of an ion exchange material as described above and / or obtainable by a method as described above for the analytical or preparative separation of analytes, preferably anions, more preferably halogenated acetic acids, most preferably for the separation of monochloroacetic acid (MCA), monobromoacetic acid (MBA), dichloroacetic acid (DCA) and dibromoacetic acid (DBA).
[0136] Another aspect of the present invention relates to a method for preparing a chromatographic column having an ion exchange material, preferably an ion exchange material as described above. The method comprises a step of adjusting the retention time of the haloacetic acid relative to a standard anion, particularly a standard anion as described herein. The retention time is adjusted by an acid group directly attached to the surface of a polymer support, wherein the acid group is selected from a sulfonic acid group, a carboxylic acid group or a combination thereof, wherein the amount of the acid group is in the range of 0.41-1.05 mmol / g of polymer support, preferably 0.65-1.05 mmol / g, particularly preferably 0.85-1.05 mmol / g; or in the range of 0.05-0.19 mmol / g of polymer support, preferably 0.05-0.16 mmol / g, particularly preferably 0.05-0.10 mmol / g.
[0137] The polymer support is preferably a polymer support as described above. The polymer support may comprise a polyamine or polymer layer as described above.
[0138] The column can be used to separate haloacetic acids relative to standard anions.
[0139] The present invention will be described in more detail with reference to the accompanying drawings and examples. The accompanying drawings and examples should not be understood as limiting. It shows:
[0140] Figure 1 : Schematic representation of steps a) to c) of the method for producing an ion exchanger according to the invention.
[0141] Figure 2: Chromatogram obtained with the ion exchange material according to Example 4.1 with 0.30 mmol / g COOH.
[0142] Figure 3 : Chromatogram obtained with the ion exchange material according to Example 4.2 with 0.36 mmol / g COOH.
[0143] Figure 4 : Chromatogram obtained with the ion exchange material according to Example 4.3 with 0.41 mmol / g COOH.
[0144] Figure 5 : Chromatogram obtained with the ion exchange material according to Example 6.0 with 0.82 mmol / g COOH.
[0145] Figure 6 : Chromatogram obtained with the ion exchange material according to Example 5.2 with 0.15 mmol / g COOH.
[0146] Figure 7 : Chromatogram of Comparative Example C having an ion exchange material without carboxylic acid groups.
[0147] Figure 8 : Relationship between the amount of LiAlH4 and carboxylic acid groups detected on the support material for Examples 2.6 to 2.9.
[0148] Fig. 9 : Selectivity factor and number of theoretical plates of dichloroacetic acid as a function of the amount of carboxylic acid groups according to Examples 2.6 to 2.9.
[0149] Fig.10 : Chromatogram of Comparative Example A.
[0150] Fig.11 : Chromatogram of Comparative Example B.
[0151] Fig.12 : Capacity change of ion exchange materials with 0.25 mmol / g COOH and 0.1 mmol / g COOH under alkaline conditions. Example
[0152] Determination of starting materials and pore size
[0153] The starting material of the following examples is PS / DVB particles. The average pore radius of the PS / DVB particles provided in step a) is determined by nitrogen adsorption in the BJH (Barret, Joyner, Halenda) model. The specific surface area is determined by nitrogen adsorption in the BET model (Brunauer, Emmett, Teller). For both analyses, a sample of 0.10945 g of PS / DVB polymer support was used. The density of the sample material is 1.105 g / cm3. The measurement was carried out in a 9 mm cell on an Autosorb iQ S / N:14713051301 instrument. The bath temperature was 77.35 K. The final degassing temperature was 60°C. The measurement evaluation was performed on Quantachrome AsiQwin version 3.01. The measurement was performed twice, once with an immersion time of 80 minutes and once with an immersion time of 40 minutes. The degassing rates were 1.0°C / min and 20.0°C / min, respectively. The average pore radius obtained by the BJH method based on pore volume is 5.1060 nm. The specific surface area calculated from the multi-point BET diagram is 540.0 m 2 / g.
[0154] Oxidation (Examples 1.1 to 1.5)
[0155] The following examples show different embodiments of the oxidation step b). However, the reaction conditions can vary within the scope of the present invention, and possible reaction conditions are summarized herein. The solvent can be acetic acid or formic acid, and acetic acid is preferred. The reaction temperature can vary from 15 to 80°C, with 80°C being a preferred temperature. The temperature ramp can be 30-120°C / h, preferably 45°C / h. As described above, the reaction is preferably carried out in the presence of hydrogen peroxide. The ratio (mol / mol) of acid to hydrogen peroxide can be in the range of 1.0: 0.12 to 1.0: 0.72, preferably 1.0: 0.14 to 1.0: 0.52, and most preferably 1.0: 0.16 to 1.0: 0.44. The reaction time can vary between 18 and 80 hours, most preferably 72 hours (h).
[0156] Example 1.1
[0157] 10.1 g of PS / DVB (55% DVB in EVB) pellets were suspended in 67 g of acetic acid and 19 g of hydrogen peroxide (35%) was added. The mixture was heated to 80°C at a temperature ramp rate of 45°C / h. The reaction mixture was stirred for 72 h, cooled and filtered. The filter cake was washed with water to a neutral pH. The filter cake was dried under vacuum at 60°C for at least 16 h.
[0158] Example 1.2
[0159] 10.5 g of PS / DVB (55% DVB in EVB) pellets were suspended in 65 g of acetic acid and 27 g of hydrogen peroxide (35%) were added. The mixture was heated to 80°C at a temperature ramp rate of 45°C / h. The reaction mixture was stirred for 72 h, cooled and filtered. The filter cake was washed with water to a neutral pH. The filter cake was dried under vacuum at 60°C for at least 16 h.
[0160] Example 1.3
[0161] 10.5 g of PS / DVB (55% DVB in EVB) pellets were suspended in 65 g of acetic acid and 24 g of hydrogen peroxide (35%) were added. The mixture was heated to 80°C at a temperature ramp rate of 45°C / h. The reaction mixture was stirred for 72 h, cooled and filtered. The filter cake was washed with water to a neutral pH. The filter cake was dried under vacuum at 60°C for at least 16 h.
[0162] Example 1.4
[0163] 10.1 g of PS / DVB (55% DVB in EVB) pellets were suspended in 64 g of acetic acid and 28 g of hydrogen peroxide (35%) were added. The mixture was heated to 80°C at a temperature ramp rate of 45°C / h. The reaction mixture was stirred for 72 h, cooled and filtered. The filter cake was washed with water to a neutral pH. The filter cake was dried under vacuum at 60°C for at least 16 h.
[0164] Example 1.5
[0165] 9.8 g of PS / DVB (55% DVB in EVB) pellets were suspended in 67 g of acetic acid and 18 g of hydrogen peroxide (35%) were added. The mixture was heated to 80°C at a temperature ramp rate of 45°C / h. The reaction mixture was stirred for 24 h, cooled and filtered. The filter cake was washed with water to a neutral pH. The filter cake was dried under vacuum at 60°C for at least 16 h.
[0166] Reduction (Examples 2.1–2.12)
[0167] The following examples show different embodiments of the partial reduction of step c). However, the reaction conditions can vary within the scope of the present invention, and possible reaction conditions are summarized herein. The reaction temperature can be from 20 to 110°C. The amount of the reducing agent can be from 0.03 g to 1.0 g, preferably from 0.05 g to 0.8 g, and most preferably from 0.1 g to 0.5 g per 1 g of dry polymer support. The reaction time can vary from 3 to 30 h. In the case of lithium aluminum hydride (LiAlH4) as a reducing agent (Examples 2.1-2.9 and 2.12), the solvent is preferably cyclopentyl methyl ether, tetrahydrofuran, toluene, wherein all solvents are dry grade (<0.1% water). In the case of sodium borohydride (NABH4) or sodium triacetoxyborohydride as a reducing agent (Examples 2.10-2.11), the solvent can be water, ethanol, methanol, tetrahydrofuran.
[0168] Example 2.1
[0169] 10 g of the dried product of Example 1.1 was suspended in 40 mL of cyclopentyl methyl ether. The mixture was heated to 70°C, after which 2.7 g of lithium aluminum hydride was added. The mixture was heated to 110°C and stirred for 18 h. The temperature was lowered to 50°C and quenched with acetone, then water. The mixture was filtered, the particles were resuspended and washed with the following solutions: acetone, tartaric acid / acetic acid solution (2.5 / 1% by weight, 47% in water), water and ethanol. The particles were dried under vacuum at 60°C for at least 16 h. The reaction produced a polymer support with 0.30 mmol / g COOH.
[0170] Example 2.2
[0171] The procedure was the same as in Example 2.1, but using the product of Example 1.2 as substrate. The reaction produced a polymer support with 0.36 mmol / g COOH.
[0172] Example 2.3
[0173] 10 g of the dried product of Example 1.2 was suspended in 40 mL of cyclopentyl methyl ether. The mixture was heated to 70°C, after which 2.3 g of lithium aluminum hydride was added. The mixture was heated to 110°C and stirred for 18 h. The temperature was lowered to 50°C and quenched with acetone, then water. The mixture was filtered, the particles were resuspended and washed with the following solutions: acetone, tartaric acid / acetic acid solution (2.5 / 1% by weight, 47% in water), water and ethanol. The particles were dried under vacuum at 60°C for at least 16 h. The reaction produced a polymer support with 0.41 mmol / g COOH.
[0174] Example 2.4
[0175] 10 g of the dried product of Example 1.2 was suspended in 40 mL of cyclopentyl methyl ether. The mixture was heated to 70°C, after which 3.3 g of lithium aluminum hydride was added. The mixture was heated to 95°C and stirred for 24 h. The temperature was lowered to 50°C and quenched with acetone, then water. The mixture was filtered, the particles were resuspended and washed with the following solutions: acetone, tartaric acid / acetic acid solution (2.5 / 1% by weight, 47% in water), water and ethanol. The particles were dried under vacuum at 60°C for at least 16 h. The reaction produced a polymer support with 0.17 mmol / g COOH.
[0176] Example 2.5
[0177] The procedure was the same as in Example 2.4, but using the product of Example 1.3 as substrate. The reaction produced a polymer support with 0.15 mmol / g COOH.
[0178] Example 2.6
[0179] 10 g of the reaction product of Example 1.4 were suspended in 40 mL of cyclopentyl methyl ether. The mixture was heated to 50°C, after which 1.8 g of lithium aluminum hydride was added. The mixture was heated to 95°C and stirred for 24 h. The temperature was lowered to 50°C and quenched with acetone, then water. The mixture was filtered, the particles were resuspended and washed with the following solutions: acetone, tartaric acid / acetic acid solution (2.5 / 1 wt %, 47% in water), water and ethanol. The particles were dried under vacuum at 60°C for at least 16 h. The reaction produced a polymer support with 0.32 mmol / g COOH.
[0180] Example 2.7
[0181] 10 g of the reaction product of Example 1.4 were suspended in 40 mL of cyclopentyl methyl ether. The mixture was heated to 50°C, after which 2.3 g of lithium aluminum hydride was added. The mixture was heated to 95°C and stirred for 24 h. The temperature was lowered to 50°C and quenched with acetone, then water. The mixture was filtered, the particles were resuspended and washed with the following solutions: acetone, tartaric acid / acetic acid solution (2.5 / 1 wt %, 47% in water), water and ethanol. The particles were dried under vacuum at 60°C for at least 16 h. The reaction produced a polymer support with 0.27 mmol / g COOH.
[0182] Example 2.8
[0183] 10 g of the reaction product of Example 1.4 were suspended in 40 mL of cyclopentyl methyl ether. The mixture was heated to 50°C, after which 3.8 g of lithium aluminum hydride was added. The mixture was heated to 95°C and stirred for 24 h. The temperature was lowered to 50°C and quenched with acetone, then water. The mixture was filtered, the particles were resuspended and washed with the following solutions: acetone, tartaric acid / acetic acid solution (2.5 / 1 wt %, 47% in water), water and ethanol. The particles were dried under vacuum at 60°C for at least 16 h. The reaction produced a polymer support with 0.19 mmol / g COOH.
[0184] Example 2.9
[0185] 10 g of the reaction product of Example 1.4 were suspended in 40 mL of cyclopentyl methyl ether. The mixture was heated to 50°C, after which 4.3 g of lithium aluminum hydride was added. The mixture was heated to 95°C and stirred for 24 h. The temperature was lowered to 50°C and quenched with acetone, then water. The mixture was filtered, the particles were resuspended and washed with the following solutions: acetone, tartaric acid / acetic acid solution (2.5 / 1 wt %, 47% in water), water and ethanol. The particles were dried under vacuum at 60°C for at least 16 h. The reaction produced 0.16 mmol / g of COOH in the polymer support.
[0186] Example 2.10
[0187] 5 g of the reaction product of Example 1.4 were suspended in 25 mL of water and 3 mL of sodium hydroxide (30% aqueous solution). 5 g of sodium borohydride were added to the suspension. The mixture was heated to 80 °C and stirred for 17 h. The reaction mixture was cooled to room temperature and 100 mL of sulfuric acid (10% aqueous solution) was added. The mixture was filtered, washed with water until pH neutral, and then washed with acetone. The particles were dried under vacuum at 60 °C for at least 16 h. The reaction produced 1.02 mmol / g COOH of the polymer support.
[0188] Example 2.11
[0189] 5 g of the reaction product of Example 1.1 were suspended in 40 mL of ethanol. 1.35 g of polyethyleneimine (Mn = 10000 Da) was added, followed by 0.25 mL of acetic acid. The mixture was stirred for 1 h, followed by 1.9 g of sodium triacetoxyborohydride. The reaction mixture was stirred for 19 h. The mixture was filtered and the filter cake was washed with water until the pH was neutral. The particles were dried under vacuum at 60 °C for at least 16 h. The reaction produced a polymer support with 0.82 mmol / g COOH.
[0190] Example 2.12
[0191] The procedure was the same as in Example 2.1 except that the reaction product of 1.5 was used. The reaction produced 0.1 mmol / g COOH.
[0192] Introduction of sulfonic acid groups (Examples 3.1 and 3.2)
[0193] The following examples show the introduction of sulfonic acid groups after step b) or c). The reaction can be carried out in acetic acid, dichloroethane or dichloromethane. Acetic acid is preferred.
[0194] Example 3.1
[0195] 17 g of the particles of Example 1.3 were reduced as described in Example 2.1, and the carboxylic acid content of these particles was 0.23 mmol / g. The particles were suspended in 100 mL of acetic acid and 20 mL of sulfuric acid and reacted for 32 seconds. Then, the reaction mixture was diluted with 50 mL of hydrochloric acid and filtered. The filter cake was washed with water, ethanol, sodium hydroxide (2 M aqueous solution), water, hydrochloric acid (1 M aqueous solution) and water until the pH was neutral. The particles were dried under vacuum at 60 °C for 16 h to obtain a product containing 0.38 mmol / g of both carboxylic acid and sulfate groups as negative charges.
[0196] Example 3.2
[0197] 20 g of the particles of Example 1.3 were reduced by suspending them in 80 mL of cyclopentyl methyl ether. The mixture was heated to 70°C, after which 5.4 g of lithium aluminum hydride was added. The mixture was heated to 110°C and stirred for 18 h. The temperature was lowered to 50°C and quenched with acetone, then water. The mixture was filtered, the particles were resuspended and washed with the following solutions: acetone, tartaric acid / acetic acid solution (2.5 / 1 wt %, 47% in water), water, and ethanol. The particles were dried under vacuum at 60°C for at least 16 h. The particles were suspended in 4 mL of sulfuric acid and reacted for 30 minutes. The reaction mixture was then diluted with 45 mL of hydrochloric acid and filtered. The filter cake was washed with water, sodium hydroxide (1 M in water), water, hydrochloric acid (1 M in water), water until the pH was neutral, and the filter cake was washed with ethanol. The particles were dried under vacuum at 60°C for 16 h to give a product containing 0.52 mmol / g of both carboxylic acid and sulfate groups as negative charges.
[0198] Introduction of a polymer layer having anion exchange groups (Examples 4.1-4.4, 5.1-5.7 and 6.1)
[0199] The following examples describe specific embodiments for incorporating a polymer layer on a polymer support.
[0200] The following reaction includes examples of forming a polymer layer from BDGE and amine, BDGE and PEI or PEI. The reaction conditions can be adjusted as follows and are not limited to the conditions provided in the examples: the amount of the polymer or polymer precursor can be 0.1 g to 10 g, preferably 0.5 g to 8.0 g, and most preferably 1.5 g to 7.0 g per 1 g of dry polymer carrier.
[0201] The reaction is preferably carried out in ethanol, water, dimethyl sulfoxide or a combination thereof. The reaction temperature is selected between 20 and 80°C, preferably 40°C for BDGE and 60°C for PEI. The reaction time is selected between 2 and 24 hours. The addition of a base is particularly used to introduce BDGE, preferably sodium hydroxide, and the reaction cycle is repeated 0 to 20 times.
[0202] The reaction conditions for introducing anion exchange groups can be summarized as follows: In the examples listed below, quaternary ammonium is added to PEI; or tertiary amine is added to BDGE. As substances for introducing quaternary ammonium, glycidyl trimethyl ammonium chloride; glycidyl methyl diethanol ammonium chloride; and glycidyl triethyl ammonium chloride can be used. As tertiary amines, N-methyl-2-pyrrolidone, N-methylmorpholine, N-methylpyrrolidone, N,N-dimethylethanolamine, N-methyldiethanolamine, N-methylpiperidine, N-ethylpiperidine, trimethylamine, triethylamine can be used. The reaction is carried out in water or dimethyl sulfoxide, the reaction temperature is 20 to 80°C, and the reaction time is 2-24 h.
[0203] The additional crosslinking step f) can be carried out in water or dimethyl sulfoxide at a temperature of 30 to 80° C., preferably 60° C., for a reaction time of 1 to 24 h, preferably 3 h.
[0204] The elimination step in the following examples can be carried out under alkaline conditions, preferably in an aqueous solution of sodium hydroxide (0.5 to 7.5 M), sodium carbonate (0.5 to 5.0 M) and potassium hydroxide (0.5 to 7.5 M), at a temperature of 20 to 100° C. and a reaction time of 2 h to 2 months (1460 h).
[0205] BDGE-PEI-ammonium ion-crosslinking
[0206] Example 4.1
[0207] 10 g of the reaction product of Example 2.1 was suspended in 31 mL of dimethyl sulfoxide and 25 mL of 1,4-butanediol diglycidyl ether. The mixture was heated to 40°C. 23 mL of water and 2.3 mL of NaOH (33% aqueous solution) were added to the reaction mixture and stirred for 5 h. The mixture was filtered and the filter cake was washed with water until the pH was neutral. The dried particles were suspended in 30 mL of a 1:4 volume / volume ethanol / water mixture. 4 g of polyethyleneimine (Mn=600 Da) was added and the mixture was stirred at 60°C for 16 h. The mixture was filtered and the filter cake was washed with water until the pH was neutral. The filter cake was dried under vacuum to obtain particles with a thick polymer layer. The particles were suspended in 100 mL of water. 14 g of glycidyltrimethylammonium chloride was added and the mixture was stirred at 60°C for 4 h. The mixture was filtered and the filter cake was washed with water until the pH was neutral. The dried particles were suspended in 200 mL of water and 18.4 mL of 1,4-butanediol diglycidyl ether was added. The mixture was heated to 60 °C and stirred for 2.5 h. The reaction mixture was filtered and the filter cake was washed with water until the pH was neutral. The filter cake was suspended in 600 mL of sodium hydroxide (1 M aqueous solution) and stirred for 16 h. The reaction mixture was filtered and the filter cake was washed with water until the pH was neutral. The particles were packed into a 4 × 250 mm PEEK column.
[0208] Example 4.2
[0209] The procedure was the same as in Example 4.1, but using the product of Example 2.2 as substrate.
[0210] Example 4.3
[0211] The procedure was the same as in Example 4.1, but using the product of Example 2.3 as substrate.
[0212] Example 4.4
[0213] The procedure was the same as in Example 4.1, but using the product of Example 3.1 as substrate.
[0214] BDGE-Amine
[0215] Example 5.1
[0216] 20 g of the reaction product of Example 2.4 were suspended in 75 mL of dimethyl sulfoxide and 50 mL of 1,4-butanediol diglycidyl ether. The mixture was heated to 40 °C and 50 mL of sodium hydroxide (1 M in water) was added. The reaction mixture was stirred for 5 h. The mixture was filtered and the filter cake was washed with water until the pH was neutral. The whole process was repeated again, after which 26.6 g of particles with a thick hydrophilic polymer layer were obtained. 15 g of these particles were suspended in a 1: 1 volume / volume mixture of dimethyl sulfoxide / water. 90 mL of N-methylpyrrolidine was added and the mixture was stirred at 70 °C for 3 h. The reaction mixture was filtered and the filter cake was washed with water until the pH was neutral. The dried particles were suspended in 100 mL of water and the mixture was heated to 100 °C. 40 mL of sodium hydroxide solution (30% in water) was added and the reaction mixture was stirred for 35 h. The mixture was filtered and washed with water until the pH was neutral. The particles were packed into a 4×150 mm column.
[0217] Example 5.2
[0218] The procedure was the same as in Example 5.1, but using the product of Example 2.5 as substrate.
[0219] Example 5.3
[0220] The procedure was the same as in Example 5.1, but using the product of Example 2.6 as substrate.
[0221] Example 5.4
[0222] The procedure was the same as in Example 5.1, but using the product of Example 2.7 as substrate.
[0223] Example 5.5
[0224] The procedure was the same as in Example 5.1, but using the product of Example 2.8 as substrate.
[0225] Example 5.6
[0226] The procedure was the same as in Example 5.1, but using the product of Example 2.9 as substrate.
[0227] Example 5.7
[0228] The procedure was the same as in Example 5.1, but using the product of Example 2.12 as substrate.
[0229] PEI–ammonium ion crosslinking
[0230] Example 6.0
[0231] 5 g of the reaction product of Example 2.11 was suspended in 20 mL of dimethyl sulfoxide and 10 g of glycidyl trimethyl ammonium chloride was added. The reaction mixture was stirred for 16 h. The mixture was filtered and the filter cake was washed with water until the pH was neutral. The dried particles were suspended in 50 mL of water and 10 mL of 1,4-butanediol diglycidyl ether was added. The reaction mixture was stirred at 60 °C for 3 h. The mixture was filtered and the filter cake was washed with water. The particles were suspended in 50 mL of sodium hydroxide (1 M aqueous solution) and stirred at 60 °C for 15 h. The particles were packed into a 4×150 mm PEEK column.
[0232] Titration method for determining the negative charge on the polymer support (COO - / SO3 - )
[0233] Example 7
[0234] The fully protonated dried particles (0.9-1.0 g) from Examples 2.1-2.9 and 3 were suspended in 20 mL portions of sodium hydroxide (0.05 M aqueous solution). The particles were shaken in the solution for 30 minutes. The suspension was centrifuged at 3800 RPM and 12 mL of the supernatant was taken with a syringe. The solution was filtered through a syringe filter (0.45 μm). Exactly 10 mL of the filtered solution was transferred to a beaker and diluted with 50 mL of ultrapure water. The solution was titrated with hydrochloric acid solution (0.05 M aqueous solution). The carboxylic acid and / or sulfuric acid content was calculated using the following equation:
[0235]
[0236] V NaOH = Volume of solution transferred (mL)
[0237] c NaOH = NaOH concentration (mol / L)
[0238] c HCl = HCl concentration (mol / L)
[0239] V EP = Volume used up to the equivalence point (mL)
[0240] m = weight of the particle (g)
[0241] Ion chromatography
[0242] Example 8
[0243] Examples 4.1-4.4 were packed in a 4×250 mm column, Example 6 was packed in a 4×150 mm column, and 9 mM KOH was used as the mobile phase, and a solution of fluoride ion, chloride ion, nitrite, bromide ion, nitrate ion, monochloroacetic acid (MCA), monobromoacetic acid (MBA), dichloroacetic acid (DCA) and dibromoacetic acid (DBA) was passed through the column at a flow rate of 0.8 mL / min at 15°C. Figure 2-5 A chromatogram obtained using such a column is shown.
[0244] Examples 5.1-5.6 were packed in a 4×150 mm column, and a solution of fluoride, chloride, nitrite, bromide, nitrate, and dichloroacetic acid (DCA) was passed through the column at 30° C. at a flow rate of 0.8 mL / min using 6:1 mM Na 2 CO 3 / NAHCO 3 as the mobile phase.
[0245] Example 5.2 was further packed in a 4×150 mm column, and 11 mM KOH was used as the mobile phase, and a solution of fluoride ion, chloride ion, nitrite, bromide ion, nitrate ion, monochloroacetic acid (MCA), monobromoacetic acid (MBA) and dichloroacetic acid (DCA) was passed through the column at a flow rate of 0.8 mL / min at 45°C. The chromatogram is shown in FIG. Figure 6 shown.
[0246] Table 1, Table 2 and Figure 7 The selectivity (α) of DCA and DBA for chloride ion listed in was calculated from the chromatogram using the following formula:
[0247]
[0248] t DCA = Retention time of dichloroacetic acid (DCA)
[0249] t Cl = retention time of chloride ion (Cl)
[0250] t DBA = Retention time of dibromoacetic acid
[0251] t0 = dead time
[0252] The theoretical plate number of DCA was calculated using the following formula:
[0253]
[0254] t DCA = Retention time of dichloroacetic acid (DCA)
[0255] W b, DCA = Peak width of dichloroacetic acid (DCA)
[0256] TP = Theoretical Plates
[0257] Determination of hydrophilicity
[0258] The hydrophilicity was determined as follows: 1 g of the hydrophilized PS / DVB particles obtained after step c) or the hydrophilized particles of Examples 2.1 to 2.9 were suspended in 20 mL of water using a Phoenix RA-VA-10 vortex mixer and the solution was shaken for 30 seconds. The particles remained suspended for 15 minutes, after which they began to settle at the bottom of the reagent tube, indicating the hydrophilicity of the particles. Reference particles PS / DVB (untreated; as provided in step a)) were subjected to the same test, but were not suspended in water, but remained on top of the water layer.
[0259] The particles obtained after step b) or examples 1.1 to 1.4, respectively, also form a suspension under the above-mentioned conditions.
[0260] Stability comparison between the ion exchange materials according to Example 5.7 and Comparative Example D
[0261] Example 9
[0262] The columns of Example 5.7 and Comparative Example D were flushed with 1 M NaOH (pH 14) at 60°C at 0.8 mL / min for 30 and 20 hours, respectively. Fig.12 As shown, at different time points, the column was flushed with water for 1 h, and the chloride ion retention time was measured with 9 mM KOH at 30°C at 0.8 mL / min. Thus, the chloride ion capacity factor was calculated by k(Cl)=(Ret(Cl)-Ret(IP)) / Ret(IP). The results are shown in Fig.12 shown.
[0263] Comparative Example
[0264] Example A
[0265] (No restore)
[0266] 10 g of the reaction product of Example 1.1 were suspended in 37.5 mL of dimethyl sulfoxide and 25 mL of 1,4-butanediol diglycidyl ether. The mixture was heated to 40 °C and 25 mL of NaOH (1 M in water) was added. The reaction mixture was stirred for 6 h. The mixture was filtered and the filter cake was washed with water until the pH was neutral. The entire procedure was repeated once more, after which the remaining epoxide was reacted with 60 mL of N-methyl-2-pyrrolidone in a 1:1 volume / volume mixture of water / dimethyl sulfoxide (120 mL).
[0267] Example B
[0268] (Partial reduction with triacetoxyborohydride and low M n Polyethylenimine (600 Da) functionalized)
[0269] 5 g of the particles from Example 1.1 were suspended in 40 mL of ethanol. 5 g of polyethyleneimine (Mn = 600 Da) were added, followed by 0.25 mL of acetic acid. The mixture was stirred for 1 h, followed by 6.3 g of sodium triacetoxyborohydride. The reaction mixture was stirred for 15 h. The mixture was filtered and the filter cake was washed with water until the pH was neutral. The particles were functionalized with anion exchange groups as described in 6.0.
[0270] Example C
[0271] (Synthesis of particles without any acid groups)
[0272] A polyvinyl alcohol (PVA) solution was prepared by dissolving 6.4 g of PVA and 0.1 g of hydroquinone in 390 mL of water. To 320 g of this solution, 2.3 g of sodium dodecyl sulfate (SDS) was added. An organic solution was prepared by mixing 14.3 g of divinylbenzene (55%), 25 g of acetoxystyrene, 29.2 g of toluene, 4.2 g of 3-methyl-1-butanol, and 0.8 g of azobisisobutyronitrile. The PVA / SDS solution and the organic solution were mixed and emulsified. Separately, 14.2 g of a polystyrene seed particle suspension (16% in water / ethanol, 70 / 30 vol / vol) was mixed with 26.4 g of the PVA solution in a reactor. The emulsion was added thereto and stirred at room temperature for 24 h. The solution was purged with argon, polymerization was started by heating the solution to 70 °C, and the reaction mixture was stirred at 70 °C for 10 h. The mixture was cooled to room temperature and the particles were filtered. The residue was washed with water, then with ethanol, water, ethanol, toluene, and acetone. The particles were dried in vacuo.
[0273] 25.7 g of the particles were suspended in 130 mL of ethanol. 21 mL of 33% sodium hydroxide solution was added to the suspension, and the solution was stirred at 45 °C for 5.5 h. The particles were washed with water until pH was neutral and rinsed with acetone. The particles were dried in vacuo.
[0274] The particles were functionalized with anion exchange groups as described in Example 5.1.
[0275] The particles were packed in a 4×150 mm column, and 11 mM KOH was used as the mobile phase, and a solution of fluoride ion, chloride ion, nitrite, bromide ion, nitrate ion, monochloroacetic acid (MCA), and dichloroacetic acid (DCA) was passed through the column at a flow rate of 0.8 mL / min at 45°C. The chromatogram is shown in FIG. Figure 7 shown.
[0276] Example D
[0277] In a 1 L reactor connected to a thermostat, 61.7 g of PS / DVB pellets were suspended in 382 mL of acetic acid. The reaction mixture was heated to 80 °C. 121 mL of hydrogen peroxide (35%) was slowly added dropwise over 2 h. The reaction mixture was stirred for 24 h, then cooled and filtered, washed with ultrapure water to neutral pH, and rinsed with ethanol. The filter cake was dried in a vacuum oven to obtain 66 g of product.
[0278] Reduction with lithium aluminum hydride: In a 1 L reactor, 51.7 g of the dried oxidation product was suspended in 196 mL of anhydrous tetrahydrofuran and cooled to 5 ° C with a thermostat. 92 mL of 2.4 M lithium aluminum hydride tetrahydrofuran solution was carefully added under stirring. The reaction mixture was heated to 55 ° C for 48 h under stirring. The reaction was stopped by cooling to 0 ° C and adding 80 ml of water within 60 minutes. Thereafter, the reaction mixture was diluted and 150 mL of sulfuric acid was added under stirring. The reaction mixture was heated to 80 ° C for 1 h and then filtered. It was washed with water to a neutral pH and rinsed with acetone. The filter cake was dried to obtain about 50 g of product. The entire procedure was repeated twice. The reaction produced 0.25 mmol / g of polymer support.
[0279] The particles were functionalized with anion exchange groups as described in Example 4.1.
[0280] Figure 1 Schematic diagram showing steps a) to c) of the method for producing an ion exchanger according to the invention. In a first step, PS / DVB particles are provided as a polymer support. The particles are subjected to an oxidation treatment in order to introduce carboxylic acid groups and other carbonyl groups into the polymer support. A partial reduction step results in a mixture of hydroxyl groups and carboxylic acid groups on the polymer support. The hydroxyl groups can react in a further step with a polyfunctional compound as a polymer or polymer precursor to form a polymer layer (step not shown).
[0281] Figure 2 The chromatogram obtained with the ion exchange material according to Example 4.1 with 0.3 mmol / g COOH is shown. The chromatogram shows the separation of the haloacetic acids, i.e. monochloroacetic acid 1, monobromoacetic acid 2, dichloroacetic acid 3 and dibromoacetic acid 4 (solid line) relative to the five standard anions fluoride, chloride, nitrite, bromide, nitrate. The haloacetic acids show good separation, with retention times of the haloacetic acids in the range of 50 minutes.
[0282] Figure 3 The chromatogram obtained with the ion exchange material according to Example 4.2 having 0.36 mmol / g COOH is shown. Figure 2 Compared to the examples shown in Figure 2, the selectivity of the haloacetic acid relative to the standard anions has changed.
[0283] Figure 4 The chromatogram obtained with the ion exchange material according to Example 4.3 having 0.41 mmol / g is shown. The haloacetic acid still shows very good separation. Figure 2 and 3 The retention time of the haloacetic acid is shorter than that of the examples shown.
[0284] Figure 5 The chromatogram obtained with the ion exchange material according to Example 6.0 having 0.82 mmol / g COOH is shown. The separation of the haloacetic acid is still good enough to be compared with Figures 2 to 4 Compared with the retention time in , the retention time of haloacetic acid is short.
[0285] therefore, Figure 2-5 The examples show the influence of the amount of carboxylic acid groups on the separation and retention properties of the ion exchange material according to the invention.
[0286] Figure 6 The chromatogram of Example 5.2 is shown, using 11 mM KOH as the mobile phase and a column temperature of 45° C. The chromatogram shows the separation of the haloacetic acids, i.e., monochloroacetic acid 1, monobromoacetic acid 2, and dichloroacetic acid 3, relative to the five standard anions fluoride, chloride, nitrite, bromide, and nitrate.
[0287] Figure 7 A comparative example of a column without carboxylic acid groups according to Example C is shown. The chromatogram shows the separation of haloacetic acids, i.e. monochloroacetic acid 1 and dichloroacetic acid 3, relative to five standard anions fluoride, chloride, nitrite, bromide, nitrate. The elution conditions are: 0.8 mL / min, 45°C, 20 mM KOH.
[0288] from Figure 6 and 7 It can be seen that Figure 6 The haloacetic acids in the solution elute earlier. Figure 6 In the chromatogram in Figure 1, MCA elutes before the chloride ions and DCA elutes within 30 minutes. For a column without any carboxylic acids, MCA elutes after the chloride ions and it takes 40 minutes to elute DCA, even though the eluent is faster than Figure 6 Therefore, it is of interest to have at least a small amount of COOH on the surface as the haloacetic acid elutes earlier, resulting in shorter analysis times.
[0289] Figure 8The relationship between the amount of lithium aluminum hydride and carboxylic acid groups detected on the support material is shown for Examples 2.6 to 2.9. Thus, it can be seen that the amount of carboxylic acid can be controlled by the amount of reducing agent added.
[0290] Fig. 9 Shown are the selectivity factors (circles) and the number of theoretical plates (triangles) for dichloroacetic acid (DCA) as a function of the amount of carboxylic acid groups according to Examples 2.6 to 2.9.
[0291] Table 1 shows the effect of changes in carboxylic acid content on the selectivity and theoretical plate number of DCA by changing oxidation conditions while keeping the reduction conditions constant (Examples 2.4 and 2.5). Measurement conditions: 6: 1 mM Na2CO3 / NaHCO3, 30°C, 0.8 mL / min.
[0292] Table 1
[0293]
[0294] Table 2 shows SO3 - / COO - group (Example 4.4) with only COO - Effect of the group (Example 4.3) on the selectivity of DCA and DBA. Measurement conditions: 9 mM KOH, 30°C, 0.8 mL / min.
[0295] Table 2
[0296]
[0297] Table 2 shows that a similar amount of negative charge generated by SO3 / COOH reduces the selectivity to DCA and DBA compared to COOH alone, and due to the pk of SO3H a Lower than COOH, accelerating the elution of these haloacetic acids to earlier retention times.
[0298] Fig.10 The chromatogram of Comparative Example A is shown. Without the reduction step and the amount of the carboxylic acid groups adjusted, the support material is not suitable for the separation of haloacetic acid. The polymer layer is not fully bonded. There are too many carboxylic acid groups, and the polymer layer has too few or even no hydroxyl groups to which it can bind, i.e. the polymer or polymer precursor connected to the carboxylic acid groups is eliminated again from the surface due to the hydrolysis step. The capacity of the column produced by the polymer layer is lost.
[0299] Fig.11The chromatogram of Comparative Example B is shown. In this example, a polymer layer is formed where the anionic and cationic groups are in close proximity, resulting in a net charge of zero in the area where ion exchange should occur. The different charges are not adequately separated spatially. Therefore, there is little interaction between the ion exchange material and the analyte solution, resulting in almost immediate elution of the anions.
[0300] Fig.12 The change in chloride ion capacity of the ion exchange material according to Example 9 is shown. This example simulates the long-term use of each chromatographic column by using a higher temperature. The higher temperature simulates the load of long-term use. As can be seen from the figure, the capacity of the 0.1 mmol / g carboxylic acid amount according to Example 5.7 remains stable over time, even after long-term exposure to the rather harsh alkaline conditions that will be used in the above-mentioned anion separation. In contrast, according to Comparative Example D, the amount of 0.25 mmol / g carboxylic acid causes the capacity to decrease over time, indicating that the column is not very stable and the material degrades to some extent after long-term use.
Claims
1. An ion exchange material for use as a stationary phase in an analytical or preparative separation process, in particular an anion, preferably a halogenated acetic acid separation ion exchange material, the material comprising - polymer carrier, - an acid group directly attached to the surface of the polymer support, wherein the acid group is selected from: a sulfonic acid group, a carboxylic acid group or a combination thereof, - a polymer layer covalently attached to the surface of the polymer support, wherein the polymer layer comprises anion exchange groups, The amount of acid groups is in the range of 0.05-1.05 mmol / g polymer carrier, preferably 0.1-0.9 mmol / g, particularly preferably 0.16-0.85 mmol / g, characterized in that The acid groups and anion exchange groups are spatially separated, preferably by at least 10 nm, preferably at least 50 nm, most preferably at least 100 nm, by the polymer layer.
2. The ion exchange material according to claim 1, wherein the polymer support is - derived at least in part from an aromatic hydrocarbon compound having at least two vinyl or allyl substituents, preferably derived at least in part from a divinylbenzene monomer; and - derived in part from a monomer selected from ethylvinylbenzene, vinyl acetate, styrene and any combination thereof; The relative amount of aromatic compounds having at least two vinyl or allyl substituents, preferably divinylbenzene derived monomers, is preferably at least 50% by weight.
3. The ion exchange material according to claim 1 , wherein the polymer layer is derived from - reaction of a polymer carrier with an oligo- or polyamine, or - Reaction of the polymer support with at least one polyfunctional compound comprising at least one first functional group reactive with amine and / or hydroxyl groups, preferably an epoxy group, and at least one second functional group reactive with amine and / or hydroxyl groups.
4. The ion exchange material according to claim 1 or 2, wherein the polymer layer is derived from - reaction of the polymer support with at least one polyfunctional compound comprising at least one first functional group reactive with amine and / or hydroxyl groups, preferably an epoxy group, and at least one second functional group reactive with amine and / or hydroxyl groups, followed by - Reaction with oligo- or polyamines.
5. The ion exchange material according to claim 3 or 4, wherein the polymer layer is crosslinked with at least one multifunctional compound, wherein the at least one multifunctional compound is selected from: - epoxides, in particular 1,4-butanediol diglycidyl ether, trimethylolpropane triglycidyl ether, poly(ethylene glycol) diglycidyl ether, resorcinol diglycidyl ether, glycerol diglycidyl ether, glycidol; - organic halogen compounds, in particular epichlorohydrin, epibromohydrin, 1,1′-oxybis[2-(2-chloroethoxy)ethane], 1,2-bis(2-chloroethoxy)ethane, bis(2-chloroethyl)ether, 1-chloro-3-iodopropane, 1,4-dibromobutane, 1,3-dibromopropane; - Aldehydes, especially glutaraldehyde.
6. The ion exchange material according to any one of claims 3 to 5, wherein the oligo- or polyamine is selected from polyallylamine, linear or branched polyethyleneimine (PEI), poly(2-methylaziridine); preferably branched PEI.
7. A method for producing an ion exchange material having an amount of acid groups in the range of 0.05-1.05 mmol / g polymer support, preferably 0.1-0.9 mmol / g, particularly preferably 0.16-0.85 mmol / g, and each acid group is spatially separated from an anion exchange group by at least 10 nm, preferably at least 50 nm, most preferably at least 100 nm, for use as a stationary phase in analytical or preparative separation processes, the ion exchange material being preferably an ion exchange material according to one of claims 1 to 6, the method comprising the following steps: a) providing a polymer carrier, b) subjecting the polymer support to an oxidation treatment in the presence of an oxidizing agent, preferably a peracid; c) partially reducing the polymer support obtained in step b) with a reducing agent to obtain a hydrophilized polymer support; d) reacting the product of step c) with at least one polymer or polymer precursor to obtain a polymer layer on the polymer support; e) introducing anion exchange groups into the polymer layer; Wherein steps c) and d) are carried out completely or partially simultaneously or sequentially.
8. The process according to claim 7, wherein the amount of peracid in step b) is generated in the presence of an acid and hydrogen peroxide, wherein the ratio (mol / mol) between the acid and H2O2 is in the range of 1.0:0.12 to 1.0:0.72, preferably 1.0:0.14 to 1.0:0.52, most preferably 1.0:0.16 to 1.0:0.
44.
9. The method according to any one of claims 7 to 8, wherein the amount of the reducing agent in step c) is in the range of 0.03 g to 1.0 g, preferably 0.05 g to 0.8 g, most preferably 0.1 g to 0.5 g, per 1.0 g of the polymer carrier obtained in step b), based on the dry weight of the polymer carrier.
10. The method according to any one of claims 7 to 9, wherein the amount of the at least one polymer or polymer precursor in step d) is in the range of 0.1 g to 10.0 g, preferably 0.5 g to 8.0 g, most preferably 1.5 g to 7.0 g, per 1 g of the polymer carrier obtained in step c), based on the dry weight of the polymer carrier.
11. The method according to any one of claims 7 to 10, wherein step e) is followed by a crosslinking step f): treating the reaction product resulting from step e) with at least one polyfunctional compound.
12. The method according to claims 7 to 11, wherein: In step e), the polymer carrier of step d) is reacted with a quaternary ammonium or tertiary amine, wherein the quaternary ammonium is preferably selected from the group consisting of glycidyl trimethyl ammonium chloride, glycidyl methyl diethanol ammonium chloride and glycidyl triethyl ammonium chloride; and the tertiary amine is preferably selected from the group consisting of N-methyl-2-pyrrolidone, N-methylmorpholine, N-methylpyrrolidone, N,N-dimethylethanolamine, N-methyldiethanolamine, N-methylpiperidine, N-ethylpiperidine, trimethylamine and triethylamine.
13. Ion exchange material for use as stationary phase in analytical or preparative separation processes, in particular chromatographic processes, obtainable by a process according to one of claims 7 to 12.
14. Chromatography column, in particular ion exchange chromatography column, filled with the ion exchange material according to one of claims 1 to 6.
15. A method for the chromatographic separation of analytes, preferably anions, more preferably halogenated acetic acids, most preferably monochloroacetic acid (MCA), monobromoacetic acid (MBA), dichloroacetic acid (DCA) and dibromoacetic acid (DBA), wherein a solution containing the analyte is contacted with an ion exchange material according to any one of claims 1 to 6, in particular passed through a chromatographic column according to claim 14.
16. Use of the ion exchange material according to any one of claims 1 to 6 and / or the ion exchange material obtainable by the process according to any one of claims 7 to 12 for the analytical or preparative separation of analytes, preferably anions, more preferably halogenated acetic acids, most preferably for the separation of monochloroacetic acid (MCA), monobromoacetic acid (MBA), dichloroacetic acid and dibromoacetic acid.
17. A method for preparing a chromatography column with an ion exchange material, preferably an ion exchange material according to any one of claims 1 to 6, comprising the step of adjusting the retention time of a halogenated acetic acid relative to a standard anion, wherein the retention time is adjusted by acid groups directly attached to the surface of a polymer support, wherein the acid groups are selected from sulfonic acid groups, carboxylic acid groups or a combination thereof, wherein the amount of the acid groups is in the range of 0.41-1.05 mmol / g polymer support, preferably 0.65-1.05 mmol / g, particularly preferably 0.85-1.05 mmol / g; or in the range of 0.05-0.19 mmol / g polymer support, preferably 0.05-0.16 mmol / g, particularly preferably 0.05-0.10 mmol / g.
Citation Information
Patent Citations
Method for modifying a polymer support material, polymer support material obtainable by such method, chromatography column, method of chromatographic separation and use of a polymer support material
EP4019126A1
Coated ion exchange substrate and method of forming
US20050181224A1
Method for producing a hydrophilic surface on ps / dvb copolymer particles
WO2020208026A1